Risk factors predicting residual lesion in subsequent hysterectomy following cold knife conization (CKC) for high-grade squamous intraepithelial lesion (HSIL) - Yong Zeng; Tao Jiang; Yahong Zheng; Jing Yang; Hua Wei; Cunjian Yi; Yan Liu; Keming Chen (BMC, 2022)
Abstract Objective To determine risk factors predicting residual lesion in a subsequent hysterectomy follow a cold knife conization (CKC) for high-grade squamous intraepithelial lesion (HSIL). Method Between January 2010 and December 2021, a total of 740 patients who underwent a hysterectomy within 3 months after CKC for HSIL were included in this study. We analyzed their demographic features and pathological parameters. A logistic regression model was used to analyze the relationship between parameters and residual lesion in subsequent hysterectomy specimens. Results 104 (14.1%) had residual lesion in the hysterectomy specimen, 3 patients with microinvasive carcinoma. The rate of residual lesion in patients with positive endocervical margin was 31.3%, with positive ectocervical margin was 15.3%, with positive combine margin was 38.6%. In multivariate analysis, positive margin (OR 4.015; 95% CI 2.526-6.381; P < 0.001), glandular involvement (OR 3.484; 95% CI 1.457-8.330; P = 0.005), HPV16/18 infection (OR 2.804; 95% CI 1.705-4.611; P < 0.001) and multiple HR-HPV infection (OR 1.813; 95% CI 1.130-2.909; P < 0.014) were independent risk factors for residual lesion. The AUC calculated by logistic regression model was 0.78. Conclusion Positive margin, positive glandular involvement, HPV16/18 and multiple HR-HPV infection were independent high risk factors of residual lesion in a subsequent hysterectomy following CKC for HSIL.